Efficiency Analysis of Factors Production Milk Fish (Chanos chanos) (Case Study on Alumni Training Participants Of Fish Culture in BPPP Banyuwangi) - . Sumartin (Airlangga University, 2017)
This study aims to analyze the economic, technical and price efficiency of milkfish farmers participating fish culture training at Center of Education and Fisheries Training Banyuwangi, analyzing covering factors affecting production efficiency. Analysis of data used in the form of production function analysis Cobb Douglas stochastic frontier which is estimated by Ordinary Least Square Method (OLS). Estimation of Cobb-Douglas production function model using OLS method to know the efficiency of the average performance of fish culture business. Estimates with the maximum likelihood (MLE) method to determining the level of technical efficiency, using the 4.7 frontier computing program developed by Coelli (1996). To know the efficiency of the price can be calculated by the value of marginal product (VMP) of production factor. The results show that the level of economic efficiency of milkfish culture business in Gresik East Java, based on the results of estimation using MLE method, the result of six factors of production is in rational area, but not yet efficient because the obtained coefficient value of each area of pond (X1) 0.318, fertilizer (X2) 0.079, lime (X3) 0.009, seeds (X4) 0.005, probiotics (X6) 0.066 and labor (X7) 1.311. While one feed production factor (X5) is in an irrational area because it has a coefficient value of -0.017. While the variables that influence inefficiency are experiential variables (Z1), age of farmers (Z2) and formal education (Z3) each have elasticity of -0.0711458; -0,6270106 and -0,1504381. The value of Marginal Product (NPM) of pond production area (X1) is 0.00059 (<1), Fertilizer (X2) is greater than 1 ie 3,01413, lime production factor (X3) 3,35338, the other NPM factor production such as Seed (X4) and Labor (X7), with value less than 1 (0.00075 and 0.03865), NPM Feed (X5), is smaller than one ie -0.00364 (<1 ). NPM probiotic (X6) is 95,1491 (> 1). Overall allocation of the seven factors of production is the average value of price efficiency is also more than one that is equal to 101,553 and economic efficiency equal to 2,904. it can be concluded that fish breeding business has not been efficient. Keywords: efficiency, economy, technical, price, frontier, milkfish